The role of Al and Co co-doping on the band gap tuning of TiO2 thin films for applications in photovoltaic and optoelectronic devices. (January 2021) - Islam, M.N.; Podder, J.
Abstract: Titanium dioxide (TiO2 ) thin film samples were synthesized with the help of a thermal spray pyrolysis method. In our investigation, the effect of Al, Co co-doping on the structural, morphological, topographical, optical, and electronic properties of TiO2 thin films were investigated. The deposited films show that as-deposited samples are nanostructured and crystallite size is varied from 66 nm to 72 nm. The structural parameters are well-matched with experimental and theoretical calculations. Energy dispersive analysis of X-rays (EDAX) spectra show that all samples are in stoichiometric conditions. The surface roughness values are varying from 66 nm to 89 nm seen by atomic force microscopy (AFM) images. The Fermi energy level tuning was investigated both experimental and theoretical simulations. The study of optical properties recognized that the absorption edge of the (Al, Co)-co-doped TiO2 sample is tuned toward the low energy region compared to the pristine sample. The calculated electrical band gap energy is matched by the optical band gap energy. A combined study of the structural, morphological, topographical, optical and electronic properties of the compound suggests that Ti1-x Al0.06 Cox O2 is a suitable candidate for optoelectronic and photovoltaic applications.